2009
DOI: 10.1016/j.eeh.2008.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Health, human capital, and African-American migration before 1910

Abstract: Using both IPUMS and the Colored Troops Sample of the Civil War Union Army Data, I estimate the effects of literacy and health on the migration propensities of African Americans from 1870 to 1910. I find that literacy and health shocks were strong predictors of migration and the stock of health was not. There were differential selection propensities based on slave status—former slaves were less likely to migrate given a specific health shock than free blacks. Counterfactuals suggest that as much as 35 percent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…That said, there is much suggestive evidence that health and other forms of human capital were complements. Better educated Blacks were more likely to leave the South before World War One but some of his reflects a positive correlation between health and education -migrants were also healthier (Logan 2009). In the early twentieth century South children of both races suffered from high rates of hookworm infection which sapped their ability to perform well in school or even to attend.…”
Section: Interpreting the Time Series: Intergenerational Transmissionmentioning
confidence: 99%
“…That said, there is much suggestive evidence that health and other forms of human capital were complements. Better educated Blacks were more likely to leave the South before World War One but some of his reflects a positive correlation between health and education -migrants were also healthier (Logan 2009). In the early twentieth century South children of both races suffered from high rates of hookworm infection which sapped their ability to perform well in school or even to attend.…”
Section: Interpreting the Time Series: Intergenerational Transmissionmentioning
confidence: 99%
“…Second, it describes a number of ways by which data have been recently revised and collected, and suggests how a national database of lynching victims might be constructed from recent efforts. While there is a fairly large literature that documents the fact that significant changes, especially racial, were taking place among African Americans following the Civil War and before the Great Migration (e.g., from Fogel and Engerman, 1974;Ransom and Sutch, 1977;Litwack, 1979Litwack, , 1998Margo, 1984;and Logan, 2009), less systematic microeconomic evidence exists to elucidate these changes and the mechanisms by which they occurred. This article aids in the quest to add more data for empirical analysis of African American life in the late 19th and early 20th centuries.…”
mentioning
confidence: 96%
“… See Bodnar et al (1982),Collins (2000),Maloney (2001),Logan (2009),Collins and Wanamaker (2014), andBlack et al (2015) for examples of research in which migrants are observed before and after moving.…”
mentioning
confidence: 99%